2019
DOI: 10.1103/physrevlett.122.110403
|View full text |Cite
|
Sign up to set email alerts
|

Avoiding Irreversibility: Engineering Resonant Conversions of Quantum Resources

Abstract: We identify and explore the intriguing property of resource resonance arising within resource theories of entanglement, coherence and thermodynamics. While the theories considered are reversible asymptotically, the same is generally not true in realistic scenarios where the available resources are bounded. The finite-size effects responsible for this irreversibility could potentially prohibit small quantum information processors or thermal machines from achieving their full potential. Nevertheless, we show her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 35 publications
(48 reference statements)
2
25
0
Order By: Relevance
“…Crucially, we have found that the correction term can vanish independently of n when a certain resonance condition between the initial and final states is satisfied. This opens the path to transformation reversibility beyond the asymptotic limit, the phenomenon that we discuss in detail in the accompanying paper [18].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Crucially, we have found that the correction term can vanish independently of n when a certain resonance condition between the initial and final states is satisfied. This opens the path to transformation reversibility beyond the asymptotic limit, the phenomenon that we discuss in detail in the accompanying paper [18].…”
Section: Discussionmentioning
confidence: 88%
“…Our results can be directly applied to the study of important problems such as entanglement distillation [16] or coherence dilution [17], but also allow one for a rigorous analysis of the irreversibility arising when finite-size resources are interconverted. Most intriguingly, we find that if a pair of states satisfies a particular resonance condition, one can achieve lossless interconversion, i.e., transformation that is arbitrarily close to reversible even for finite n. In the accompanying paper [18] we discuss how this effect can be employed to avoid irreversibility, which directly affects, e.g., the performance of heat engines working with finite-size working bodies [19]. This paper is structured in the following way.…”
Section: Introductionmentioning
confidence: 99%
“…When catalytic transformations with correlations are allowed, the mathematical condition governing the feasibility of a transformation becomes a simple entropic condition. In the various resource theories listed in the table, p refers to different objects: for entanglement theory, it denotes the Schmidt coefficients; for coherence, the incoherent coefficients; and for thermodynamics, the block-diagonal energy coefficients (see, e.g., [33]). We have placed question marks in the table entries that have not been explored (to the best of our knowledge).…”
Section: Related Workmentioning
confidence: 99%
“…Although important insights have been obtained in trying to connect the information-theoretic and fluctuation theorem approaches [17,18], they have, so far, not been explicitly related to dissipation. Resource-theoretic analysis of dissipation was performed independently [19][20][21][22], where the authors investigated irreversibility of thermodynamic processes due to finite-size effects. However, these results were obtained for quasi-classical case of energy-incoherent states, and so they are not able to account for quantum effects that come into play when dealing with even smaller systems, when fluctuations around thermodynamic averages are no longer just thermal in their origin.…”
Section: Introductionmentioning
confidence: 99%